Effects of Oral Repetition on Learners’ Japanese Word Accentuation - Yoshida, Kayo; Fukada, Atsushi (IALLT Journal of Language Learning Technologies, 2014)
Japanese word accentuation is a problematic area for learners unfamiliar with a pitch accent system. Since accent locations are unpredictable, learners are typically told to memorize them by rote, which is a time-consuming, tedious, and demanding task. It would certainly be ideal for learners to learn correct accentuation without explicit instruction as they learn new words. This article reports on a preliminary study that examined effects of a computer-based online word repetition exercise on the learning of Japanese word accentuation. 41 students in their 10th week and 17 students in their 12th week in a 2nd-year 1st-semester Japanese course took a pretest, followed by computer-based online word repetition practice on the Speak Everywhere system, a posttest immediately after the practice, and a delayed posttest after one week (class-and-computer condition). Out of the same group of students now in a 2nd-year 2nd-semester course, 22 students took a pretest, followed by two posttests in their 5th week (class-only condition). A paired t-test (two tailed) performed on 13 overlapping subjects found a significant difference between the two conditions (t=5.58, p<.001, Cohen’s d =1.9309). The online word repetition practice produced a significant gain in accentuation scores without explicit instruction, while classroom instruction alone was not sufficient to produce a significant gain.